Investigating Secondary School Music Teachers' Views about Online Music Lessons During the COVID-19 Pandemic - Akarsu, Sıtkı (Pen Academic Publishing, 2021)
In education systems, learning/teaching activities designed based on a specific curriculum for a specific age group are carried out following a work schedule. As long as conditions permit, the work schedule continues without interruption. However, crises such as pandemics disrupt this schedule and lead to problems in the planning and timely-execution of educational processes. The present study aimed to investigate secondary school music teachers' views about online music lessons during the COVID-19 pandemic and to offer outputs that will contribute to the implementation of distance education activities, which are expected to be more widespread in the future.  The study employed the general screening model. The study group comprised 24 music teachers working in the central district of Kastamonu, a city in the north-west of Turkey. An interview form was developed to obtain the music teachers' views about the conduct of online lessons. Necessary permissions were obtained, and the interview form was distributed to the participants via e-mail. The data obtained from the interview forms were tried to be interpreted within theme tables by taking the opinions of the experts. The study employed the content analysis method, one of the qualitative data analysis methods. The study found that the majority of secondary school music teachers thought that distance education was not suitable for music lessons. It was also determined that most of the participants had no prior experience with distance education, had difficulty using instruments in online lessons, and had synchronization problems in all music activities. Furthermore, internet connection problems, low motivation on the student side, the inefficiency of online lessons, digital fatigue, and the risk of children being exposed to harmful content on the internet emerged as other problems encountered by the participants.
Keywords: 4. Education; 16. Peace & justice; 3. Good health